Estabilidade de colunas de material compósito reforçado por fibras - D'Aguiar, Savanna Cristina Medeiros (2017)
The use of composite materials in the construction industry has excelled in recent years, as a result of your high rigidity and resistance, low density, flexible manufacturing, among other advantages over traditional materials. On the other hand, the mechanical behavior of these structures is more complex than the metal structures, mainly because of the orthotropy. This complexity increases when it has been considered laminated columns - composed of several laminae, with different materials and fiber orientation. Therefore, the present work aims to perform a theoretical and computational study of the behavior, performance and resistance of laminated and pultruded columns of fiber reinforced composite material. For this, analysis models were proposed, using the Finite Element Method (FEM), considering the effects of physical and geometric nonlinearities. Column collapse was evaluated using the First Ply Failure (FPF) approach, using different failure criteria, and the nonlinear physical behavior was simulated from a continuous damage model. Additionally, it was checked the applicability of expressions available in the literature to determine the loading capacity of these structures, including the interaction between local and global buckling. A validation of the models of analysis was made on the basis of numerical and experimental results of other researches, obtaining a good agreement. Based on the analysis, the influence of the lamination scheme and thickness on the behavior of laminated columns was confirmed, and the efficiency based of the FPF approach was confirmed, as well as the feasibility of some expressions proposed in the literature to predict the load capacity of columns of fiber reinforced composite material. In general, the results that were obtained evidenced the use of computational analysis as a way to contribute to the studies of stability and resistance of columns of composite material.